Aldosterone Pathway Blockade to Prevent Atrial Fibrillation: A Systematic Review and Meta-Analysis. (15th March 2017) - Neefs, J.; van den Berg, N.W.E.; Limpens, J.; Berger, W.R.; Boekholdt, S.M.; Sanders, P.; de Groot, J.R.
Abstract: Background: Despite advances in therapeutic interventions AF remains a progressive and symptomatic disease. Therefore, novel therapeutic interventions targeting the underlying arrhythmogenic substrate for AF is needed. Atrial fibrosis is an important component of the arrhythmogenic substrate of AF and may be initiated by aldosterone binding to the mineralocorticoid receptor. We hypothesized that aldosterone pathway blockade with mineralocorticoid receptor antagonists (MRA) reduces atrial fibrosis, and thus AF. Methods: We searched OVID MEDLINE, OVID EMBASE and the Cochrane Central Register of Controlled Trials from inception to June 10th, 2016 for randomized controlled trials (RCT) and observational studies addressing MRA and providing information on AF occurrence. Two independent reviewers selected and appraised the data. We performed random-effects meta-analyses. Summary odds ratios (OR) with 95% confidence intervals (CI) were calculated. Results: We included 14 studies, 5 RCT and 9 observational cohorts, with a cumulative number of 5332 patients (male: 74.9%, age: 65.3 years); 2397 (45.0%) received an MRA (spironolactone or eplerenone). During follow-up, 204 (8.5%) patients treated with MRAs, developed AF, compared to 547 (18.6%) patients, without MRA treatment. Meta-analyses showed a significant overall reduction of AF risk in MRA treated patients (OR: 0.48 CI: 0.38–0.60 p < 0.001), including a reduction of new-onset AF (OR: 0.52 CI: 0.37–0.74 p < 0.001) and recurrent AF (OR: 0.37 CI: 0.24–0.57 p < 0.001), but not post-operative AF (POAF) (OR: 0.60 CI: 0.33–1.09 p = 0.09). Conclusions: MRAs significantly reduce new-onset AF and recurrent AF, but not POAF. MRA treatment can be considered an additive therapeutic strategy in AF. Graphical abstract: